God's Scribe : The Historiographical Art of Galbert of Bruges - Rider, Jeff, 1954- (Book collections on Project MUSE., 2001)
"Scholars have long considered the De multro to be a true journal, written hastily as events unfolded and never revised. In God's Scribe, the first book devoted to Galbert and his chronicle, Jeff Rider challenges that view. He argues that the De multro is not the transparent and objective testimony it has been taken to be; rather it is a complex and sophisticated work of astonishing originality that is an outstanding example of medieval historical writing." "Intended as a companion volume to the De multro, the book provides an outline of the Flemish crisis of 1127-28 and summarizes what is known about Galbert. It traces the elaboration of the multro from a set of wax notes to a nearly completed chronicle. Rider studies Galbert's sources, the way he took and organized his notes, the distinct stages in which the chronicle was written, its literary qualities, and the conceptual tools he used to comprehend the events he related in it. Rider concludes that Galbert's efforts to understand an extended series of events in a light of the theology of history and authority common in his day, and to apply that theology to the practice of historical writing, made the De multro one of the most intellectual and experimental histories of its time, while its style, form, and viewpoint made it one of the most popular ones."--Jacket